Allozyme differentiation among allopatric populations of Anopheles nuneztovari (Diptera: Culicidae) - Scarpassa, Vero Margarete; Tadei, Wanderli Pedro [UNESP]; Suarez, Marco Fidel (My University, 1996)
Four enzymes in six geographic populations, four Brazilian and two Colombian, of Anopheles nuneztovari were studied. There were differences among the most frequent alleles in the EST5, ACON and MDH loci in the populations from Brazil and Colombia. The α-GPD(*)C allele was encountered very frequently in the Palo/Sit population in Colombia and the α-GPD(*)B allele was found to be fixed in most of the Brazilian populations. An additional α-GPD band was found only in Palo/Sit. The considerable genetic differentiation between populations in western Colombia vs. Brazil suggests that a certain degree of reproductive isolation exists between them.
Keywords: alloenzyme; enzyme; allele; anopheles; brazil; colombia; controlled study; gene frequency; genotype; geographic distribution; nonhuman; reproduction